Immunology - C. Vaman Rao (New Delhi Narosa Publishing House, 2006)
Earlier published as An Introduction to Immunology, this second edition with a shorter title has been enlarged to deal with recent concepts and ideas in immunology with respect to phylogeny and evolution of the immune system, origin of antigen binding receptors, complement pathway and MHC. The book also includes recent information on: Role of CpG motifs, heat shock proteins, epithelial cells, Toll like receptors in innate immunity and role of dendritic cells, gd T cells and mucosal layer in acquired immunity. Recent understanding of regulation of immunoglobulin gene, recombination mechanism, regulation of immune response, neural regulation, regulatory T-cells, CD8+memory cells. Concepts on cross presentation of antigens, role of heat shock proteins in antigen presentation, pathogenesis of atopic dermatitis, genetics of asthma, mechanism of food allergy, role of T-cells in atopic and contact allergy. Gives an insight into mechanism of immune tolerance to foetus, regulatory T-cells in transplantation, immune tolerance, gene therapy in transplantation, xenotransplantation. Information on recent developments in genetic modulation of tumor antigens, anticancer vaccines, DNA fusion gene vaccine for cancer therapy. Information on initiation of autoimmunity, role of CD4+ and regulatory CD4+ cells, interferon, genetics, and chemokines in autoimmunity, chemotherapy and antigen based therapy for autoimmunity. New strategies to counter HIV and acquired immunodeficiency syndrome, Exercises and summary at the end of each chapte Table of Contents Preface to the Second Edition / Preface to the First Edition / Introduction / Innate Immunity / Acquired Immunity (Adaptive Immunity) / Cells and Organs of Immune System / Antigens or Immunogens / Major and Minor Histocompatibility Complex / Antibodies (Immunoglobulins) / Antigen Antibody Interactions / Organization and Expression of Immunoglobulin Genes / B-Cell Maturation, Activation and Differentiation / T-Cell Maturation, Activation and Differentiation / T-Cell and B-Cell Receptors / Antigen Processing and Presentation / Effector Responses of Cell-Mediated and Humoral Immunity / Cytokines / Complement System / Vaccines / Immune Response to Infectious Diseases / Hypersensitivity / Transplantation Immunology / Immunologic Tolerance / Immunology of Tumors / Autoimmune Diseases / Immunodeficiency Diseases / Glossary / Index
Keywords: Immunology